Accounting for false‐positive acoustic detections of bats using occupancy models. Issue 5 (1st July 2014) - Clement, Matthew J.; Rodhouse, Thomas J.; Ormsbee, Patricia C.; Szewczak, Joseph M.; Nichols, James D.; McKenzie, Ailsa
Summary Acoustic surveys have become a common survey method for bats and other vocal taxa. Previous work shows that bat echolocation may be misidentified, but common analytic methods, such as occupancy models, assume that misidentifications do not occur. Unless rare, such misidentifications could lead to incorrect inferences with significant management implications. We fit a false‐positive occupancy model to data from paired bat detector and mist‐net surveys to estimate probability of presence when survey data may include false positives. We compared estimated occupancy and detection rates to those obtained from a standard occupancy model. We also derived a formula to estimate the probability that bats were present at a site given its detection history. As an example, we analysed survey data for little brown bats Myotis lucifugus from 135 sites in Washington and Oregon, USA. We estimated that at an unoccupied site, acoustic surveys had a 14% chance per night of producing spurious M. lucifugus detections. Estimated detection rates were higher and occupancy rates were lower under the false‐positive model, relative to a standard occupancy model. Un‐modelled false positives also affected inferences about occupancy at individual sites. For example, probability of occupancy at individual sites with acoustic detections but no captures ranged from 2% to 100% under the false‐positive occupancy model, but was always 100% under a standard occupancy model. Synthesis and applications. Our results suggest that false positives sufficient to affect inferences may be common in acoustic surveys for bats. We demonstrate an approach that can estimate occupancy, regardless of the false‐positive rate, when acoustic surveys are paired with capture surveys. Applications of this approach include monitoring the spread of White‐Nose Syndrome, estimating the impact of climate change and informing conservation listing decisions. We calculate a site‐specific probability of occupancy, conditional on survey results, which could inform local permitting decisions, such as for wind energy projects. More generally, the magnitude of false positives suggests that false‐positive occupancy models can improve accuracy in research and monitoring of bats and provide wildlife managers with more reliable information.